Leadership styles and their effect on employees: a comparative study of two Mediterranean tourism destinations - Ayse Atar Yilmaz; Ece Konaklioglu (Tourism & Management Studies)
The primary objective is to correlate the relationship between the variables in order to determine the effect of leader behaviour on organisational silence, organisational silence on organisational cynicism and organisational cynicism on psychological well-being. The study also aims to foreground the difference with respect to these variables in two countries chosen as the sampling universe and draw a comparative analysis of the leadership types adopted by the manager of hospitality organisations in respective countries and personnel's attitude toward the respective hospitality organisations they work for. Research population consists of 4 and 5-star hospitality organisations operating in different centers of Turkey and Italy. Comparative analyses were conducted based on the findings of whether the said variables in this intercultural study between Turkey and Italy offered any intercultural difference among the employees in hospitality organisations. It surfaced that, except for organisational silence, there existed a difference in all other variables. Besides, cyclical model pertaining to emergent variables in the study exposed a different dimension of this study. In the light of all these findings, suggestions that could hold both theoretical and practical values for the researchers as well as practitioners were provided.